Influence Of Organizational Culture, Leadership And Job Satisfaction On Lecturers Organizational Commitment In State Islamic University of North Sumatra - Ojak Manurung; Syahyunan Syahyunan; Saskia Saskia (LPPPIPublishing, 2022)
This study aims to answer the problems of the four proposed hypotheses, which include: 1) Does organizational culture affect lecturers' organizational commitment; 2) Does leadership affect the organizational commitment of lecturers; 3) Does job satisfaction affect lecturer's organizational commitment; 4) Do organizational culture, leadership and job satisfaction together affect the organizational commitment of lecturers. The population in this study were all lecturers at nine faculties in the Islamic University of North Sumatra, amounting to 332 people with a total sample of 186 people taken using the Krecji table. The research instrument is a questionnaire with a Likert scale. The research data were processed and analyzed by simple and multiple regression analysis. The results of the analysis show that: 1) Organizational culture affects the organizational commitment of lecturers, this indicates that the higher the organizational culture, the higher the organizational commitment of the lecturers; 2) Leadership affects the organizational commitment of lecturers, this indicates that the better the leadership, the higher the organizational commitment of the lecturers; and 3) Job satisfaction has an effect on lecturers' organizational commitment, this indicates the higher job satisfaction, the higher the lecturer's organizational commitment.